La mise en question de l’arbitrage d’investissement et la réforme du règlement des différends entre investisseurs et États - Sucharitkul, Vanina (Université Paris 2, 2022)
Au cours des dernières décennies, le régime de règlement des différends entre investisseurs et États (« RDIE »), par le biais de l’arbitrage ad hoc, a été l’objet d’un examen approfondi et de critiques croissantes. Au fur et à mesure que les États défendeurs de diverses régions ont perdu des affaires d’arbitrage d’investissement, ils ont été comme désenchantés par ce type de mécanisme de résolution des litiges, dans ce qui est désormais connu comme le contrecoup de l’arbitrage d’investissement. Plus récemment, ces critiques se sont intensifiées au point que l’Union Européen a remplacé le RDIE contemporain par une cour permanente d’investissement pour régler ces différends. Une approche intermédiaire de la réforme du système par l’établissement d’un organe d’appel visant à donner de la cohérence aux nombreuses sentences arbitrales ad hoc est également envisagée. Cette thèse analyse les principales critiques du système du RDIE actuel afin d’examiner sa pertinence et effectue une comparaison entre les options de réforme, la manière dont elles sont censées résoudre les défauts du système, ainsi que les implications découlant de certaines des solutions les plus débattues. L’objectif de la thèse est de faire valoir qu’une refonte radicale ou révolutionnaire du système d’arbitrage des investissements ne fera que générer des incertitudes, susciter des problèmes juridiques et pratiques très complexes, et ne n’apportera finalement pas de meilleurs résultats. L’accent devrait plutôt être mis sur une indispensable évolution ou réforme substantielle au niveau des traités, afin de tirer les leçons des cas passés et de s’assurer que la rédaction des traités répond mieux aux défis actuels. = The dispute settlement regime between investors and States through ad hoc arbitration has come under heavy scrutiny and mounting criticism in the past few decades. As respondent States in various regions have lost investment arbitration cases, those States have become disenchanted with this form of dispute resolution mechanism in what has become known as the backlash against investment arbitration. More recently, these critiques have escalated to the extent that the European Union has replaced it with a completely new scheme that includes dismantling the investment arbitration system by replacing it with a permanent investment court to settle such disputes in its trade agreement. An intermediate approach to reforming the system, the establishment of an appellate body aimed at providing consistency to the numerous ad hoc arbitration awards, is also being considered. This thesis analyses the main criticisms of the current investor-State dispute settlement (“ISDS”) system to determine its validity and carries out a comparison between the policy reform options, how they are intended to solve the system’s purported flaws, as well as the implications arising from some of the hotly debated options. The aim of the thesis is to argue that drastic overhaul or revolutionary reform to the investment arbitration system will only lead to uncertainties, more complex legal and practical problems and would not yield better results. Instead, the focus should be on the evolution of substantive reform at the treaty level, to address the lessons learned from past cases and ensure that treaty drafting responds to current day challenges.
Keywords: Appellate Mechanism; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Convention CIRDI; Cour Multilatérale d’Investissement; Droit et État; Groupe de travail III de la CNUDCI; ICSID Convention; INVESTMENTS; ISDS; ISDS Reform; Incohérence de sentences arbitrales; Inconsistent Arbitral Awards; Investissements étrangers (droit international); Investisseurs et État; Investment Court System; Investor-State Dispute Settlement; Multilateral Investment Court; Mécanisme d’appel; RDIE; Règlement des différends; Règles de transparence; Réforme du RDIE; Système de Cour d’Investissement; Transparency Rules; UNCITRAL Working Group III

La négociation dans le règlement des litiges internationaux d'investissement - Paredes Balladares, Francisco Xavier (Université Paris 1, 2022)
La négociation est une institution fascinante du droit de l’investissement, polyvalente et multifonctionnelle. L’étude systématisée de la négociation dans le droit de l’investissement fait ressortir que cette institution est plus qu’un simple moyen permettant de parvenir à des accords. En réalité, la négociation est partout dans le droit de l’investissement. Il s’agit de la seule institution véritablement transversale au droit des investissements, qui intervient de nombreuses manières dans les rapports entre les investisseurs et les États d’accueil. Nous pouvons attester de l’existence des négociations avec la négociation des accords internationaux d’investissement ou de contrats d’investissement entre l’État d’accueil et l’investisseur. De surcroît, la négociation est un instrument au service de l’instance juridictionnelle qui sert aux arbitres dans l’interprétation des accords ainsi que pour la détermination de la responsabilité des parties. Si les divers rôles de la négociation dans le droit de l’investissement ont fortement contribué à l’évolution du droit international, la négociation reste une institution peu connue. Sa nature, sa portée, et son contenu juridique restent peu étudiés et non systématisés dans le droit de l’investissement. De ce fait, cette recherche offre une analyse approfondie de la négociation afin de trouver sa place dans l’ordre juridique de l’investissement (en général) et dans le règlement des litiges (en particulier). Nous examinerons dans cette recherche les nombreux apports de la négociation au droit de l’investissement permettant d’affirmer que la négociation constitue le mécanisme essentiel dans la conclusion des accords ; qu’elle impose aux parties des comportements précis ; qu’elle est un instrument qui permet aux tribunaux internationaux de déterminer la responsabilité des parties en fonction de leurs actions et inactions ; enfin, qu'elle constitue un instrument qui aide la justice arbitrale à interpréter les accords ponctuels. Ainsi, cette recherche a pour ambition de comprendre la nature, la portée et les fonctionnalités de la négociation dans le règlement des litiges transnationaux d’investissement. Negotiation is a fascinating instrument of Investment Law, versatile and rich in legal content. The systematic study of negotiation in Investment Law reveals that this institution is much more than just an instrument for reaching agreements. In fact, negotiation is everywhere. It is the only institution of Investment Law that is truly transversal, intervening in many layers of the relationship between investors and Host States. We can recognize the existence of negotiations from the very beginning of an investment process (the negotiation of a contract between the investor and the Host State), as well as negotiations over the course of the life and operation of an investment, and negotiations at the termination of a transnational investment project. Moreover, negotiation is an instrument that serves arbitral tribunal as element for the interpretation of the agreements, and the determination of the parties’ liability. The various roles of negotiation in Investment Law have certainly contributed to the evolution of international law. Nevertheless, negotiation remains an unknown institution to lawyers, regarding its nature, scope, uses and legal content. Investment law requires a thorough analysis of this institution and a structure that adapts to the transnational legal order. In this research, we will examine numerous contributions of negotiation to Investment Law: as a necessary mechanism for the conclusion of agreements that impact Investment Law; as a mandatory rule that it imposes specific behaviors on the parties in respect to the principle of good faith; as an instrument that serves international tribunals to determine the parties’ liability for their actions taken over the course of negotiations, and as an instrument to assist the justice system to construe contracts. Thus, the ambition of this research is to comprehend the nature, scope, and the features of negotiation in International Investment Law. La negociación es un instrumento fascinante de Derecho de las inversiones, a la vez versátil y rico en contenido legal. El estudio sistematizado de la negociación en el Derecho de las inversiones revela que esta institución es mucho más que un instrumento para alcanzar acuerdos. En realidad, la negociación está en todas partes en el derecho de las inversiones. Es laúnica institución verdaderamente transversal al Derecho de las inversiones, que interviene de varias formas en la relación entre inversionistas y los Estados receptores de inversión. Podemos constatar la existencia de las negociaciones desde el inicio de un proceso de inversión (en la negociación de un tratado bilateral deinversión, o de un contrato entre el inversionista y el Estado anfitrión), negociaciones durante la vida y la operación de una inversión y negociaciones encaminadas a la terminación o liquidación de la inversión transnacional. Resalta, además, que la negociación es un instrumento al servicio de la instancia jurisdiccional, que sirve a los árbitros en su tarea de interpretación de acuerdos, y a la determinación de la responsabilidad de las partes. Los diversos roles que presenta la negociación en el Derecho de las inversiones ciertamente han contribuido a la evolución del Derecho internacional. Sin embargo, la negociación sigue siendo una institución poco conocida por los juristas, especialmente en lo tocante a su naturaleza, alcance, usos y contenido legal. ElDerecho de las inversiones requiere de un análisis exhaustivo de esta institución, acompañado de una estructura que se adapte al orden legal transnacional.En esta investigación examinaremos las diversas contribuciones que hace la negociación al Derecho de las inversiones, a saber: se muestra como un mecanismoinevitable para concluir acuerdos que terminan contribuir en la evolución del Derecho de las inversiones; impone a las partes comportamientos específicos enrespeto del principio de la buena fe; es un instrumento para que los tribunales internacionales determinen la responsabilidad de las partes en razón de sus accionesdurante la fase de negociación y se constituye en un instrumento que asiste al sistema de justicia en la tarea de interpretar los acuerdos. La ambición de esta investigación no es otra cosa que comprehender la naturaleza, el alcance y la funcionalidad de la negociación en el Derecho internacional de las inversiones.
Keywords: Accord; Arbitrage; Arbitrage d'investissement; Arbitration; Bonne foi; Buena fe; Contenido jurídico; Contract interpretation; Contrahendo; Contrato; Derecho Internacional Público; Derecho de las Inversiones; Droit de l’investissement; Droit international; Duty to negotiate; Estoppel; Good faith; Interpretación de acuerdos; Interprétation de l’accord; Investissements étrangers; Investment Law; Investments; Justicia; Negociación; Negotiando; Negotiation; Negotiation agreement; Négociation; Négociations; Obligación de negociar; Obligation de négocier; Pacto de negociación; Pactum; Período de negociación; Public International Law; Transnacional; Transnational

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

L'équilibre des intérêts en droit international des investissements : principe général de droit applicable aux rapports entre investissement et environnement - Mekpo, Cosme Gosshé (Université Laval, 2022)
Avec la résurgence des problèmes environnementaux, le droit international des investissements se retrouve aujourd'hui face à l'urgence de sa propre réadaptation. Et, comme réponse unique à un impératif catégorique, l'équilibre des intérêts émerge en tant qu'un principe général de droit (PGD), de nature souple et autonome, à qui ses diverses fonctions (logique, axiologique, unificatrice et correctrice) confèrent une utilité opérationnelle au sein de l'ordre juridique international, et dont la mise en œuvre en droit international des investissements est l'expression de la dimension évolutive. En tant que principe référentiel, il est consubstantiel au droit international des investissements et vise à faire prévaloir un idéal normatif (le droit de l'équilibre) sur un autre (le droit de la protection). Toutefois, l'aporie de l'équilibre des intérêts est d'être, à la fois, une affirmation du principe de la souveraineté réglementaire et une limitation de celui-ci. Dans un premier temps, sa mise en œuvre se traduit par la prise en compte de l'intérêt général dans le balancier état-investisseur et, dans un second temps, cette exigence ne se concrétise qu'au bout d'un double test de la proportionnalité et du raisonnable. Alors que sa source de régénération par rapport au reste du système est la protection internationale des valeurs fondamentales et socio-environnementales, sa structure de base demeure le couple droit-obligation et s'apparente à une transversalité normative qui combine à la fois la lex lata et la lex ferenda d'une part, la soft law et la hard law d'autre part. Malgré sa fécondité croissante, il est possible de le décrire comme étant la source d'un droit poly-normatif et « open-textured » qui possède à la fois un noyau d'applicabilité, une teneur variable et une juridicité foisonnante. Le profil abrégé de cette construction normative pourrait alors se matérialiser en droit international des investissements par: la prise en compte de l'intérêt général, la responsabilité sociale des entreprises multinationales, la réciprocité par équivalence des droits et obligations des parties, la flexibilité réglementaire et la compatibilité d'avec les autres normes de protection internationales.
Keywords: Dommages à l'environnement; Investissements; Investissements étrangers (environnement); Investments; Responsabilité Sociale de l'Entreprise

Articulating clearer fair and equitable treatment clauses within Tanzania’s international investment agreements: correcting the disparity between host state and international investor interests - Ntangeki, Joanitha (Canterbury Christ Church University, 2022)
International Investment Agreements seek to promote foreign investment whilst protecting foreign investors. Despite the goal of International Investment Agreements being to secure parity between the interests of the host State and the foreign investor, there has been consequential disparity in the protection of the interests of both parties. Notably, the host State is susceptible to disadvantage. This research examines the extent to which International Investment Agreements in Tanzania have facilitated this disparity. In particular, the research evaluates the inclusion of fair and equitable treatment provisions in Tanzania’s International Investment Agreements and the extent to which fair and equitable treatment provisions have in some way facilitated this disparity. The research examines systematically the fair and equitable treatment provisions contained in twenty IIAs signed by Tanzania between 1965 and 2013 (eleven of which are still in force). The research takes a comparative approach in evaluating and contrasting the Tanzanian provisions with other fair and equitable treatment clauses in IIAs signed by India, Morocco and the Netherland. The Tanzanian provisions are vague and non-uniform in comparison. The research is situated in the broader context of national sovereignty and the relationship between Tanzania and its foreign investors under international law. The substance of the analysis centres on foreign investors in the mining sector in Tanzania and the extent to which these investors have sought to take advantage of the fair and equitable treatment clauses in the IIAs in order to pursue their activities to the detriment of local populations. The research evidences the negative impact of their claims that changes in government policy (often aimed at benefiting citizens) amount to unfair treatment of the foreign investor. This has a significant impact on the ability of the government to develop its policies around sustainable development, environmental protection and the guarantee of human rights of the citizens of the host State. The research demonstrates that a clearer and fuller articulation of fair and equitable treatment clauses within Tanzania’s IIAs can act as a corrective to the disparity between the host State and the international investor. This requires that IIAs are drafted to include an exhaustive and full list of the State’s obligations towards the foreign investor so as to limit foreign investor claims against the host State. The impact of not doing so has grave implications for the rights of the citizens of Tanzania and unnecessarily tips the balance of power in favour of the foreign investor and away from the host State. This undermines the ability of the host State to assert its sovereignty within its own borders.
Keywords: Foreign investment; International investment; Investor interest; Tanzania